Chemopreventive properties and toxicity of kelulut honey in Sprague Dawley rats induced with azoxymethane - Saiful Yazan, Latifah; Muhamad Zali, Muhamad Firdaus Shyfiq; Mohd Ali, Razana; Zainal, Nurul Amira; Esa, Nurulaidah; Sapuan, Sarah; Yong, Sze Ong; Yin, Sim Tor; Gopalsamy, Banulata; Fui, Ling Voon; Syed Alwi, Sharifah Sakinah (Hindawi Publishing Corporation, 2016)
Ethnopharmacological Relevance. Colon cancer has been a major problem worldwide. Kelulut honey (KH) is produced by the stingless bees from Trigona species and has strong antioxidant activities that could be one of the potential chemopreventive agents from natural resources. Aim of This Study. This study investigated the chemopreventive properties and toxicity of KH in Sprague Dawley rats induced with azoxymethane (AOM). Material and Method. Twenty-four male Sprague Dawley rats aged 5 weeks were divided into 4 groups: (G1) untreated group not induced with AOM, (G2) untreated group induced with AOM, (G3) treated group induced with AOM, and (G4) treated group not induced with AOM. Injection of AOM (15 mg/kg) was via intraperitoneal route once a week for two subsequent weeks. The treatment groups were given oral administration of KH (1183 mg/kg body weight) twice daily for 8 weeks. Results. Treatment with KH significantly reduced the total number of aberrant crypt foci (ACF) and aberrant crypts (AC) and crypt multiplicity. KH was not toxic to the animals since the level of blood profile parameters, liver enzymes, and kidney functions was in normal range. Conclusions. The current finding shows that KH has chemopreventive properties in rats induced with colorectal cancer and also was found not toxic towards the animals.